Diabetes insipidus in pregnancy. (28th January 2018) - Quigley, James; Shelton, Cliff; Issa, Basil; Sripada, Sreebala
Abstract : Key content: There are various types of diabetes insipidus that occur due to different pathology that occurs outside of, during, and as a result of pregnancy. All pregnant women presenting with polyuria and polydipsia should be investigated with blood tests including urea and electrolytes, calcium levels and thyroid function tests. Plasma and urine osmolality can also be helpful in making the diagnosis. Additional symptoms that are suggestive of diabetes insipidus secondary to other underlying pathology (e.g. a pituitary tumour) are likely to require radiological imaging. Women diagnosed with diabetes insipidus should have regular consultant review in clinic with monitoring of serum electrolytes. They should also receive an antenatal anaesthetic review. A multidisciplinary approach should be adopted during labour and they should be managed on delivery suite with senior obstetric and anaesthetic input. Pre‐eclamptic toxaemia (PET) and haemolysis, elevated liver enzymes and low platelets (HELLP) can exacerbate diabetes insipidus as hepatic dysfunction leads to a reduction in vasopressinase metabolism. Furthermore, it has been suggested that pituitary hypoperfusion due to this syndrome could also be a cause of gestational diabetes insipidus. These women present a therapeutic challenge as they are in a volume‐depleted state as a consequence of DI, however they require judicious fluid management because of their PET. Early detection and effective management will reduce morbidity and mortality in both the mother and fetus. Untreated or undiagnosed, it has the potential to have serious consequences for the expectant mother and fetus. Learning objectives: To understand the different subtypes of diabetes insipidus, their pathophysiologies and their effects during the ante‐, peri‐ and postnatal periods. To appreciate that diabetes insipidus can herald the onset of underlying hepatic dysfunction with associated serious maternal and fetal consequences arising from both the biochemical abnormalities associated with diabetes insipidus and the secondary problems of impaired liver function. To appraise the current theories of the link between PET and diabetes insipidus.